Postsynaptic Assembly: A Role for Wnt Signaling - Stamatakou, Eleanna (Dev Neurobiol, 2014)
Synapse formation requires the coordinated formation of the presynaptic terminal, containing the machinery for neurotransmitter release, and the postsynaptic side that possesses the machinery for neurotransmitter reception. For coordinated pre- and postsynaptic assembly signals across the synapse are required. Wnt secreted proteins are well-known synaptogenic factors that promote the recruitment of presynaptic components in diverse organisms. However, recent studies demonstrate that Wnts act directly onto the postsynaptic side at both central and peripheral synapses to promote postsynaptic development and synaptic strength. This review focuses on the role of Wnts in postsynaptic development at central synapses and the neuromuscular junction. © 2013 The Authors. Developmental Neurobiology Published by Wiley Periodicals, Inc. Develop Neurobiol 74: 818–827, 2014